Multiple sclerosis diagnostic delay and its associated factors in Upper Egyptian patients - Eman M. Khedr; Islam El Malky; Hussein B. Hussein; Doaa M. Mahmoud; Ayman Gamea (Scientific Reports, 2023)
Abstract The earlier the diagnosis of multiple sclerosis (MS), the sooner disease-modifying treatments can be initiated. However, significant delays still occur in developing countries. We aimed to identify factors leading to delayed diagnosis of MS in Upper Egypt. One hundred forty-two patients with remitting relapsing MS (RRMS) were recruited from 3 MS units in Upper Egypt. Detailed demographic and clinical data were collected. Neurological examination and assessment of the Disability Status Scale (EDSS) were performed. The mean age was 33.52 ± 8.96 years with 72.5% of patients were females. The mean time from symptom onset to diagnosis was 18.63 ± 27.87 months and the median was 3 months. Seventy-two patients (50.7%) achieved diagnosis within three months after the first presenting symptom (early diagnosis), while seventy patients (49.3%) had more than three months delay in diagnosis (delayed diagnosis). Patients with a delayed diagnosis frequently presented in the period before 2019 and had a significantly higher rate of initial non-motor presentation, initial non-neurological consultations, prior misdiagnoses, and a higher relapse rate. Another possible factor was delayed MRI acquisition following the initial presentation in sixty-six (46.5%) patients. Multivariable logistic regression analysis demonstrated that earlier presentation, initial non-neurological consultation, and prior misdiagnosis were independent predictors of diagnostic delay. Despite advances in MS management in Egypt, initial non-neurological consultation and previous misdiagnoses are significant factors responsible for delayed diagnosis in Upper Egypt.